Real-world comparison of lisocabtagene maraleucel and axicabtagene ciloleucel in large B-cell lymphoma: an inverse probability of treatment weighting analysis with 3-year follow up - Portuguese, Andrew J.; Huang, Jennifer J.; Jeon, Yein; Taheri, Mahnoosh; Albittar, Aya; Liang, Emily C.; Hirayama, Alexandre V.; Kimble, Erik L.; Iovino, Lorenzo; Poh, Christina; Gopal, Ajay K.; Shadman, Mazyar; et al. (Haematologica (Roma), 2025)
Lisocabtagene maraleucel (liso-cel) and axicabtagene ciloleucel (axi-cel) are FDA- and EMAapproved chimeric antigen receptor (CAR) T-cell therapies for relapsed/refractory large B-cell lymphoma (LBCL). However, comparative real-world analyses of their efficacy and toxicity with extended follow-up are lacking. We conducted a retrospective study of 160 LBCL patients treated at the Fred Hutchinson Cancer Center with commercial liso-cel or axi-cel per standard of care. Using inverse probability of treatment weighting (IPTW) to mitigate treatment allocation bias and multivariable adjustments to minimize other sources of confounding, we assessed the impact of CAR T-cell product type on outcomes. Axi-cel was associated with significantly higher rates of cytokine release syndrome (CRS; G1+: adjusted OR [aOR] 4.27, p=0.004; G2+: aOR 2.88, p=0.006), immune effector cell-associated neurotoxicity syndrome (ICANS; G1+: aOR 2.10, p=0.048), and immune effector cell-associated hematotoxicity (ICAHT; G1+: aOR 8.09, p